ART Adherence Measurement in Non-Clinical Settings in South India - Kleinman, Nora J. (AIDS Care, 2014)
Optimal adherence to antiretroviral therapy (ART) is key to viral suppression, but may be impeded by psychosocial consequences of HIV-infection such as stigma and depression. Measures of adherence in India have been examined in clinic populations, but little is known about the performance of these measures outside clinical settings. We conducted a cross-sectional study of 151 Tamil-speaking people living with HIV/AIDS (PLHA) in India recruited through HIV support networks and compared single item measures from the Adult AIDS Clinical Trial Group (AACTG) scale, a visual analog scale (VAS), and a question on timing of last missed dose. Depression was measured using the Major Depression Inventory (MDI) and HIV-related stigma was measured using an adaptation of the Berger Stigma Scale. Mean age was 35.6 years (SD±5.9); 55.6% were male; mean MDI score was 11.9 (SD±9.1); and mean stigma score was 67.3 (SD±12.0). Self-reported perfect adherence (no missed doses) was 93.3% using the AACTG item, 87.1% using last missed dose, and 83.8% using the VAS. The measures had moderate agreement with each other (kappa 0.45 - 0.57). Depression was associated with lower adherence irrespective of adherence measure used, and remained significantly associated in multivariable analyses adjusting for age and marital status. Stigma was not associated with adherence irrespective of the measure used. The VAS captured the greatest number of potentially non-adherent individuals and may be useful for identifying PLHA in need of adherence support. Given the consistent and strong association between poorer adherence and depression, programs that jointly address adherence and mental health for PLHA in India may be more effective than programs targeting only one.